Perspective of Homoeopathy in Modulation of Absolute Eosinophil Count and Pulmonary Function Test in Bronchial Asthma - A Research Study (Advancements in Homeopathic Research, 2022)
Allergic bronchial asthma is a respiratory disease which is triggered by allergens with evidence of increased level of absolute eosinophil count with decreased levels of FEV1, FVC and FVC/FEV1. 40 diagnosed patients of bronchial asthma with increased levels of absolute eosinophil count and reduced pulmonary function were selected for the study. The study period was between 01.03.2013 and 30.09.2014. Swel lab 920 EO+ is used for confirmation of absolute eosinophil count and Helios 401 spirometerusedfor assessing FEV1, FVC and FVC/FEV1levels. Kruskal Wallis test and Wilcoxon signed rank test were used for the statistical analysis. In this study it was found that homoeopathic medicines are having capacity to reduce the levels of absolute eosinophil count and improve the lung function among bronchial asthma patients.
Keywords: Allergic bronchial asthma; Absolute eosinophil count; Pulmonary function test; Forced expiratory volume in 1 sec; Forced vital capacity